ETNIS NIAS DI KOTA PADANG TAHUN 1970-2008 : SUATU TINJAUAN SEJARAH SOSIAL BUDAYA - -, Ardiman - (Pendidikan Sejarah, 2014)
This thesis focuses on the social and cultural life of the people ofNias in Padang. Although as ethnic immigrants in the city of Padang, but their presence in the community who contributed to Padang as that has opened up areas in the city of Padang. Ethnic Nias in Padang lot to contribute to the progress of the city of Padang, where their presence opens up new areas in the city of Padang. Writing this thesis uses methods of social history, which connects ethnic Nias in Padang Minangkabau society both from public life and relationships of cultural assimilation among the people of Nias culture brought from the region of origin with the community in Minangkabau culture. The method used in this study include, first stage of gathering resources (Heuristic), Second stage of criticism Source criticism both internal and external criticism, three stages of interpretation in which this phase commit an understanding of the sources to be studied, and the last stage of Historiography, is the writing stage of research re<;.;u s. The source used is a source of primary and secondary sources. Writing this thesis uses methods of social history, which connects ethnic Nias in Padang Minangkabau sociely both from public life and relationships of cultural assimilation among the people ofNias culture brought from the region of origin with the community in Minangkabau culture. The method used in this study include, first stage of gathering resources (Heuristic), Second stage of criticism Source criticism both internal and external criticism, three stages of interpretation in which this phase commit an understanding of the sources to be studied, and the last stage of Historiography, is the writing stage of research results. The source used s a source of primary and secondary sources.